Religious Activities of Anak Siak: A Case Study of Madrasah Tarbiyah Islamiyah Canduang Sumatera Barat - Septria Fadli, Muhammad (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
This study discusses a boarding school that is a place of Anak Siak‘s value internalization. Anak Siak is a designation for male students in the surrounding community. The boarding school has a strong influence on Anak Siak in terms of spiritual, intellectual, and social aspects for better or worse. To direct these three dimensions in a better direction, the boarding school dormitory needs to be filled with religious activities that can support Siak children in shaping their personalities. This research uses descriptive qualitative research methods using data collection techniques, interviews, observation, and documentation study. The results showed that religious activities are activities related to activities that aim to increase individual spirituality on a religious basis. On the other hand, the religious activities of Anak Siak in the main dormitory are designed as well as possible to achieve the vision and mission set by the dormitory supervisor, the vision and mission of the dormitory are also derived from the vision and mission of the MTI boarding school. So, the religious activities carried out in the MTI Canduang main dormitory are divided into three, namely daily, weekly, and special activities.